2019
DOI: 10.1001/jama.2018.20484
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Expansion Gains Momentum

Abstract: Health care was rated one of the key issues for voters in the 2018 midterm elections, according to exit polls. The election results set the stage for as many as 500 000 low-income individuals in the United States to gain coverage through new state Medicaid expansions under the Affordable Care Act (ACA). Expansion could occur in 5 additional states: 3 through ballot measures (Idaho, Nebraska, and Utah) and 2 through the election of new governors supportive of expansion (Kansas and Maine). If all 5 states expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…6 Medicaid has expanded substantially with the passage of the Affordable Care Act, with an increase in the number of individuals covered from approximately 50 million in 2010 to an estimated 76 million by 2020, as additional states have indicated that they will expand Medicaid. 7 Across these payers, how does the United States spend $3.5 trillion in health care dollars? Various estimates are available, but overall, hospitals account for approximately 33% of spending, 1,2 physician and clinical services approximately 20%, 1,2 and prescription drugs (including retail, ambulatory, and hospital costs) about 18%.…”
Section: Viewpoint Page 1661mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Medicaid has expanded substantially with the passage of the Affordable Care Act, with an increase in the number of individuals covered from approximately 50 million in 2010 to an estimated 76 million by 2020, as additional states have indicated that they will expand Medicaid. 7 Across these payers, how does the United States spend $3.5 trillion in health care dollars? Various estimates are available, but overall, hospitals account for approximately 33% of spending, 1,2 physician and clinical services approximately 20%, 1,2 and prescription drugs (including retail, ambulatory, and hospital costs) about 18%.…”
Section: Viewpoint Page 1661mentioning
confidence: 99%
“…Although children represent approximately 44% of Medicaid recipients (34 million of a total of 72 million), they account for only approximately 19% of the cost . Medicaid has expanded substantially with the passage of the Affordable Care Act, with an increase in the number of individuals covered from approximately 50 million in 2010 to an estimated 76 million by 2020, as additional states have indicated that they will expand Medicaid …”
mentioning
confidence: 99%
“…And a fundamental question—is health care a right or privilege?—remains unanswered. While many in the United States receive exceptional care and about 20 million fewer individuals are uninsured following enactment of the Affordable Care Act (ACA), the number of uninsured is again increasing, now close to an estimated 27.5 million or 8.5% of the US population . Financial support for health and health care is also a growing challenge for low-, middle-, and high-income countries around the world.…”
mentioning
confidence: 99%
“…One of the great successes of the Affordable Care Act has been the expansion of Medicaid. In large part due to this expansion, the number of individuals in the United States with health care coverage has increased by about 25 to 30 million since 2011; following midterm elections, it is likely that additional Medicaid expansion will occur …”
mentioning
confidence: 99%